Isolation and Characterization of Bacteria from Siam Citrus Leaves with Scab Symptoms - Mela, Mela; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Scab disease on leaves can reduce Siam citrus production. Aims of this study is determine the genus of bacteria in rhizosphere against bacteria isolated from scabies symptomatic. The research has been carried out in the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural sciences, Universitas Tanjungpura. Characterization was carried out morphologically and physiologically. The macromorphology observed is shape, edges, color and elevation. The micromorphological characters observed were shape, arrangement, color and gram type. The physiological characters observed were urease, glucose, lactose, sucrose, catalase, citrate, MR, ornithin, indole, motility, type of fermentation and H²S formation. The results of the isolation obtained 3 genus are Xylophilus sp. (BKS 1), Burkholderia sp. (BKS 2) dan Xylophilus sp. (BKS 3).The bacterial genus isolation results obtained can be used for antagonistic testing with other bacteria.